2022
DOI: 10.1038/s41598-022-14254-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bioflavonoid-containing mouth rinses on optical properties of tooth-coloured dental restorative materials

Abstract: This study investigated differences in colour (ΔE00) and translucency parameter (ΔTP00) of nanofilled/microhybrid composites and a glass-ionomer cement following immersion in bioflavonoid (Citrox)- or chlorhexidine-based mouth rinses. Sixty disc-shaped specimens (N = 5/group) of Filtek Supreme (3M), Gradia Anterior (GC) and Fuji IX (GC) were exposed to Citrox/0.2%CHX (Perio+0.2, Curaprox), Citrox/0.09%CHX (Perio+0.09, Curaprox), 0.2%CHX (Savacol, Colgate-Palmolive) or distilled water by 2-min agitation daily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…They concluded that flowable composite had the lowest surface roughness, whereas the flowable compomer had the greatest. [ 36 ] The study has some drawbacks, including a small sample size and limited immersion techniques. In addition, larger-scale investigations will be done on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that flowable composite had the lowest surface roughness, whereas the flowable compomer had the greatest. [ 36 ] The study has some drawbacks, including a small sample size and limited immersion techniques. In addition, larger-scale investigations will be done on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…L * = 25.87, a * = −1.12 and b * = 0.95 are the CIE values for the black setting, while L * = 69.79, a * = 0.03 and b * = 2.70 are the CIE values for the white setting. The following formula was used to calculate the TP 00 for each specimen 47 :
Figure 4 The color measurement. ( A ) The photometer unit of the spectrophotometer device, ( B ) the middle of the facial surface of the specimen fixed on the outer surface of the holder (4-mm diameter), ( C ) the holder with the specimen positioned in its place inside the spectrophotometer, and ( D ) back and white plasticine covering the specimen during measurements.
…”
Section: Methodsmentioning
confidence: 99%
“…L * = 25.87, a * = −1.12 and b * = 0.95 are the CIE values for the black setting, while L * = 69.79, a * = 0.03 and b * = 2.70 are the CIE values for the white setting. The following formula was used to calculate the TP 00 for each specimen 47 B − H ′ W represents the difference in hue under black and white settings. The rotation factor and the weighting function are given by R T and S. The parametric factors are indicated by K L , K C , and K H .…”
Section: Color and Translucency Measurement (After Cementation) A Ref...mentioning
confidence: 99%
“…However, this composite is also relevant in terms of color stability due to its chromogenic potential, causing brown stains on the teeth, tongue and on silicate and resin composite restorations [ 9 ]. Several staining mechanisms have been described for chlorhexidine such as its degradation to release parachloraniline, non-enzymatic browning reactions, denaturation of proteins by chlorhexidine with formation of metal sulfide and precipitation of anionic dietary chromogens by cationic antiseptics [ 3 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…CHX present in mouthwashes could affect the color stability of resin composite restorations [ 9 ], even more so if other factors contribute to pigment retention on the resin composite surface. Therefore, a coarse-to-fine-grained polishing system needs to be applied in order to test whether a considerable color variation in nanohybrid resin composites can be avoided [ 5 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%